Regulation and termination of NADPH oxidase activity - DeCoursey, T. E.; Ligeti, E. (Cellular and molecular life sciences : CMLS, 2005)
NADPH oxidase of phagocytes plays a crucial role in host defense by producing reactive oxygen species (ROS) that are intended to kill invading microbes. Many other cells produce ROS for signaling purposes. The respiratory burst oxidase in human neutrophils is the main but not exclusive subject of this review, because it is archetypical and has been studied most extensively. The activity of this enzyme must be controlled in phagocytes to prevent collateral damage, and in non-phagocytic cells to perform its signaling role. With many stimuli, NADPH oxidase activity is transient. Various forms of evidence indicate that sustained NADPH oxidase activity requires continuous renewal of the enzyme complex, without which rapid deactivation occurs. This review considers mechanisms that have been proposed to terminate the phagocyte respiratory burst. Changes in the phosphorylation state of p47(phox) and in the species of nucleotide bound to Rac seem to be the dominant factors in deactivation.